The development and empirical testing of an innovative quality improvement program to improve nurses' work environments in Philippines - Paguio, Jenniffer Torralba
Sustainable human resources for health in supportive organizational environments are essential to optimizing healthcare services. Extensive evidence has reinforced the impact of healthy nurse work environments on patient safety, reduction of missed care and adverse events, reduction of hospitalization costs and stay, and nurses' job performance, burnout, satisfaction, and retention. However, there is limited evidence on specific strategies that are applicable in settings with heavy workloads and limited resources like nursing workforce source countries such as the Philippines.; This study developed and investigated the effects of a teamwork enhancement and quality improvement program on the nurses' work environment (NWE), job satisfaction, burnout experience, intention to leave, and perceived quality of care provided; and explored the nurses' perceptions about the NWE improvement program and their experiences throughout the intervention period. A preliminary phase through a narrative synthesis identified the existing scope of knowledge on strategies to improve NWE in the hospital context and identified the more crucial design characteristics for more favorable outcomes.; Phase 1 is a countrywide, cross-sectional, sequential mixed-methods study that explored the NWE in the Philippines. The Donabedian model of quality of care underpinned the association between the structural, process, and outcome aspects of NWE. In particular, this phase examined the ability of the more modifiable process variables to moderate between unfavorable effects of non-modifiable NWE structural variables on nurses' outcomes. Using a qualitative approach, this study also further explained how the NWE structural and process aspects shape the nurses' outcome. As informed by the results of Phase 1, insights from the preliminary narrative synthesis and literature review, an innovative program titled "Nurturing Effective Teamwork and Continuous Quality Improvement" (NET-CQI) program was developed to improve the NWE. The program involved a teamwork enhancement training using Team Strategies and Tools to Enhance Performance and Patient Safety (TeamSTEPPS 2.0®), and the implementation of quality improvement projects using the Model for Improvement to identify priority unit issues and change ideas, and tested using the Plan-Do-Study-Act cycle focused at enhancing nurse autonomy, leadership and management support, teamwork, and workload management.; Phase 2 was a quasi-experimental study that examined the effects of NETCQI on overall NWE. The changes in various outcomes between the two study groups over six months were compared using the Generalized Estimating Equation (GEE) model. These include the outcomes of nurse's job satisfaction burnout, perceived quality of care, and its impact on the nurses' autonomy, perception towards the received leadership and management support, and nurses' relationship with physicians. For the preliminary phase, the systematic review included 14 studies on interventions aimed at improving NWE. Initiatives were categorized into educational, accreditation, and participatory approaches. Based on the Donabedian model's ability to explore how the intervention characteristics related to the outcome, the review found that intervention that used a participatory approach as a unit-based strategy to strengthen the process aspects of NWE appeared to be more effective against outcomes. Specifically, the use of the participatory approach was able to enhance nurses' job satisfaction, autonomy and leadership, reduce turnover intent and nurse overtime, enhance patient satisfaction and decrease injuries related to falls and medication errors.; Understanding that NWE improvement interventions are context-specific, Phase 1 sought to understand the context of NWE in Philippine government hospitals where the succeeding phase planned for intervention testing. The study recruited 990 nurses from seven randomly selected end-referral hospitals across the archipelago, with the response rate as 75.47%. The NWE was fair and characterized by an exceedingly high bed occupancy rate, understaffing, moderate patient acuity, meager salary, low professional autonomy, and limited management support, with at least 25% intended to leave in the next six months. However, nurses did not perceive themselves as burned out and had moderate job satisfaction. Moderation analysis indicated that NWE process characteristics of nurse autonomy and good nursephysician relations were able to moderate the high patient acuity toward the improved perceived quality of care. Qualitative findings generated six key themes to describe the NWE. The themes include: (a) 'Self-initiated coping for heavy workload jeopardized patient safety and quality of care'; (b) 'Professional status threatened by the unsafe and unhealthy work environment.'; (c) 'Unfair work arrangement and employment status weaken the nurse' desire to stay.'; (d) 'Rigid hierarchical organization culture that aggravates job stress and worsens collegial relationship.'; (e) 'Unresolved internal conflict relating to heavy workload triggers burnout; and (f) Sense of meaning and fulfillment in the journey of professional development and practices. Mixed-methods analysis using meta-matrix confirms the congruence of the generated themes across nurse levels and supported by quantitative analysis results.; As for the Phase 2 study, 71 nurses from 13 matched units received NETCQI, while others (n = 70) received usual care. The mean age of the nurses at 35 years (SD ± 9.35), with 62.41% permanently employed, working for an average of 7.65 years, with an average workload of 15 patients per shift, and spending 1 hour on overtime. The attrition rate was 13.46%. At baseline, study groups significantly differed on nurses’ characteristics educational attainment (p = 0.004), engagement in life-long learning (p = 0.037) and nursing position (p = 0.045) favoring the control group. Contradictory to the hypothesis, the results indicated that the NET-CQI did not significantly improve the nurse outcomes and process aspects of NWE over the six-month evaluative period. Process evaluation showed that the experience of the sudden increase in workload due to staffing changes and the experience of a disease outbreak among the intervention group midway through the intervention implementation, as well as organization-level improvements in the control units, might have contributed to the non-significant effects. Nevertheless, the qualitative data indicated that the nurses who participated in the NET-CQI experienced increased professional autonomy, support from nursing leadership and hospital management, and enhanced relationships with physicians. Apart from the high acceptability of the NET-CQI program, nurses in the intervention groups cited heavy workload, poor staffing, and conflicting priorities as major barriers to the implementation of the NET-CQI project. At the same time, QI mentorship and training, and support from hospital administration were facilitators.; The findings indicate the acceptance and feasibility of NET-CQI in a workload-burdened health care setting in the Philippine. Despite issues on contextual conduciveness due to threats of history have generated bias in the study findings of lack of statistically significant effects on NWE, the positive narratives from the nurses still imply the potential of the NET-CQI program in improving the process and outcome aspects of NWE. Future studies may need to investigate its more long-term effect with a larger sample in an administratively more stable environment.; 人力資源有助優化醫療服務。研究指出良好的護理工作環境有助提升患者的安全、護士的工作效率、滿意度和留職意欲, 以及能減少醫療失誤、患者的住院開支和時間。可是，現時缺乏研究去改善工作量繁重和資源有限的護理工作環境，這對菲律賓等護理勞動力出產國尤其重要。; 這項研究深入探討團隊協作和質量改進計劃對護理工作環境、工作滿意度，工作倦怠，離職意願及護理服務質素的影響；並了解護士在改進計劃期間的經歷及對計劃的意見。研究的初步階段先利用文獻綜述，綜合了現時改善醫院環境的策略，並確定了關鍵的干預設計特徵。研究的第一階段為一項全國性、橫向、序列混合設計，旨在了解菲律賓醫院的護理工作環境。 Donabedian的護理質量模型強調護理工作環境中結構，過程和結果之間的關係。本研究使用定性方法了解護理工作環境中的結構和過程如何影響護理質素。在第一階段，根據文獻綜述中得出的結果，設計了一個名為「NET-CQI」的計劃，以改善護理工作環境。計劃包括使用TeamSTEPPS©進行團隊合作培訓，並使用改進模型來實施質量改進項目，以識別需優先處理的問題，並利用「Plan-Do-Study-Act」循環去加強護士的自主權、領導力、團隊合作以及工作量管理。第二階段為一項準實驗研究，以了解NET-CQI對護理工作環境的影響, 並利用廣義估計方程（GEE）比較了兩個組別在六個月內的變化。研究變數包括護士工作滿意度、護理質量的感知、自主權、對獲得的領導和管理支持的感知以及醫護關係。在初步階段，文獻綜述綜合了14項針對改善護理工作環境的研究，分別採用教育，認證和參與式介入。參照Donabedian模型去了解干預特徵與結果之間的關係，此階段發現參與式介入最為有效。參與式介入能夠提高護士的工作滿意度，自主權、領導力和患者的滿意度，並能減低離職意圖、加班時間及醫療失誤。; 第一階段的研究旨在了解菲律賓政府醫院中的護理工作環境，其後進行干預測試。研究合共招募了990名護士，回應率為75.47％。研究發現菲律賓政